Material-Mind-Method: On the Teaching of Reference Assignment Deadlines: Helpful or Not?. Issue 3 (2nd October 2021) - Roy, Loriene
ABSTRACT: Setting deadlines may help motivate students to complete their work. In addition to describing class policies, instructors can employ a number of strategies to assist students in meeting deadlines.